Stereological analysis of spermatogenesis in Brycon orbignyanus (Characiformes: Bryconidae) - Benevente, Cristiane Fernanda [UNESP]; Quirino, Patricia Postingel [UNESP]; Gomes-Silva, Luciane [UNESP]; Delgado, Maria Luiza Ribeiro [UNESP]; Bianchini, Bárbara Correa [UNESP]; de Freitas, Guilherme Antônio; Ninhaus-Silveira, Alexandre [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP] (Hindawi, 2022)
Piracanjuba, Brycon orbignyanus, is an important rheophilic species for aquaculture studies on genetic diversity, spermatogenesis, semen cryopreservation and taxonomy. Due to anthropic actions its population has been declining, resulting in the loss of natural stocks, thus pushing the species to near extinction. No stereological analysis of spermatogenesis in piracanjuba has been performed. The present study aimed to evaluate spermatogenesis in B. orbignyanus using stereological analysis to quantify the number of germ cells and Sertoli cells, spermatogonial generations, spermatogenesis yield, meiotic index and the percentage of cell death. Testes of five 1-year-old B. orbignyanus specimens were collected, fixed in 2.5% glutaraldehyde and 4% paraformaldehyde and processed for light microscopy. Three types of spermatogonia were identified. Based on the number of B spermatogonia per cyst, it was estimated that spermatogonia underwent approximately nine mitotic divisions before differentiating into primary spermatocytes. Three types of spermatids were identified. In the final spermatid cyst, there were 1204 germ cells, indicating a spermatogenic yield of 58%. An increase in germ cells resulted in a subsequent increase in the number of Sertoli cells, with growth halted at the spermiogenic phase. Thus, stereological analysis of spermatogenesis is essential for better understanding of the reproductive processes in this species.
Keywords: meiotic index; Piracanjuba; Sertoli cell; spermatogenic yield; spermatogonial generation; stereology